PEMANFAATAN LIMBAH KELAPA DALAM MENINGKATKAN EKONOMI MASYARAKAT DESA JAYA BHAKTI KECAMATAN ENOK UNTUK MENDUKUNG PELESTARIAN LINGKUNGAN DITENGAH PANDEMI COVID-19 - Andriansyah Putra; ANDRIANSYAH (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2021)
The purpose of this research is to increase the utilization of coconut waste in Jaya Bhakti Village, Enok District, Indragiri Hilir Regency during the Covid-19 period to support environmental conservation. The method used in this study is a qualitative descriptive method or describes all aspects of existence. This descriptive qualitative method is a method used to seek knowledge about the object of research at a certain point in time. The results of the discovery of coconuts that can be used in the surrounding environment can pay attention to the economic downturn of the community and employment opportunities in the community using the Covid-19 method, helping the community maintain and increase community creativity so that it can slightly improve the community's economy during the COVID-19 pandemic.